Pendidikan Islam di Kesultanan Turki Usmani, 1300-1922 M - Fitriasari, Mufida (Syams, 2023)
Education as a dimension of the development of a nation, during the Ottoman era, is quiteinteresting to analyze its existence. Because behind the glory of its expansion there has beenacute intellectual lethargy. Considering that they were a military nation, the Ottoman Turksfocused more of their activities in the military field, while in the field of science, they did notappear to be as prominent. For this reason, in this article, the author focuses on thedevelopment of education during the Ottoman era. This is interesting to analyze, because theOttoman Empire has carved a long history in Islamic history as a whole. Panulis wanted tosee the sides of the Ottoman Empire, which led to the rise of this kingdom amidst thedestruction of other Islamic kingdoms. The Islamic education system under the OttomanEmpire was dominated by institutions such as madrasas, kuttabs, and ribaths. Madrasahsare the main centers of learning, which not only teach Islamic sciences, but also generalsciences such as mathematics, astronomy and philosophy. The Islamic education curriculumat that time was also comprehensive and integrated. This research uses a type of libraryresearch (Library Research) with descriptive methods and a historical approach. Researchersuse data collection techniques with documentation techniques, namely reviewing librarysources such as journals, educational books, history books and other relevant sources. Thisarticle discusses, describes and analyzes Islamic education in the Ottoman Empire.